Integrating Deep Learning and a Love-Based Curriculum to Enhance Meaningful Learning in Islamic Primary Education - Rivaldi Agung Ramadhani; Abd Muhith; Moh Sutomo (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
This study explores how deep learning can be integrated with a love-based curriculum to enhance meaningful learning in Islamic primary education. Although scholars have widely discussed deep learning as a student-centered approach and linked love-based education to character and relational development, limited empirical research has explored how schools combine these two educational approaches to promote meaningful learning. Using a qualitative case study design, the researchers conducted the study at Madrasah Ibtidaiyah Negeri 3 Jember, Indonesia. They collected data through classroom observations, semi-structured interviews, and document analysis involving the school principal, teachers, students, and parents. The researchers analyzed the data using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings show that integrating deep learning with a love-based curriculum fostered more active participation, deeper contextual understanding, reflective thinking, and collaborative meaning-making among students. At the same time, the values of empathy, care, respect, and emotional support fostered a safe, positive classroom climate that strengthened students' motivation, confidence, and social interaction. Instructional leadership, teacher collaboration, and parental involvement supported the implementation of this approach. This study contributes to the development of an integrative pedagogical framework that connects cognitive engagement with affective and relational values in Islamic primary education. The findings suggest that caring relationships and value-oriented classroom practices can strengthen meaningful learning when they support student-centered pedagogy.